Comparative Analysis of Hidden Web Crawlers - Kumar, Ashok; Mahajan, Manish; Singh, Dheerendra (International Journal of Computer Sciences and Engineering, 2025)
Huge data on the internet is not available for the crawler of surface web to index. It can be accessed through search forms when required. This data cannot be accessed by using the hyperlinks present in a web page. Research on hidden web mainly focus on exploring ways to access databases that are usually present behind the search forms. The main effort was to put on how to fill the searched forms with meaningful values. This paper compares different type of hidden web crawler to mention the features and shortcomings.